Pelatihan Pembuatan Green packaging Untuk Pembungkus Sayuran Hidroponik Mom’s Farm yang Ramah Lingkungan di Kampung Nagrek - Silalahi, Agustinus; Natalia, Christine; Prasetya, Wibawa; Lictyawati, Marcellina Cynthia (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2021)
Product packaging is an image or description of an object that protects and is an essential element in sales. Packaging design and packaging form have an essential role in influencing consumer decisions to buy a product. The better the packaging displayed by the company, the more consumers will decide to choose and buy the product. Mom's Farm, a joint effort between residents of Nagreg Village in Sampora Village and Unika Atma Jaya, which is engaged in urban farming, realises the importance of preserving the environment. This business produces daily hydroponic vegetables such as mustard greens and lettuce. Replacing the old plastic packaging with green packaging, from banana leaves, will attract more buyers because the products use unique and environmentally friendly packaging. Finally, in addition to benefiting from the vegetables consumed, buyers can also contribute directly to reducing plastic waste and supporting environmental conservation. This community service activity aims to provide insight into the importance of preserving the environment through green packaging and assisting in making packaging from banana leaves. The planned activity has done well, and the participants can quickly follow the teaching of making packaging from banana leaves. Furthermore, based on the results of the feedback questionnaire, the participant's assessment also showed that overall, the informants received good and excellent scores in delivering the material.